Effect of a major highway on the spatial and temporal variation in the structure and diversity of the avifauna of a tropical premontane rain forest - Ávalos, Gerardo; Bermúdez, Esteban (Revista de Biología Tropical, 2016)
Roads immersed in conservation areas will increase in number, size, and traffic over the next decade, and thus, understanding their effects on forest-dependent wildlife is crucial for improving current management practices and reducing the negative impacts of roads on sensitive species. We examined the influence of route 32 (a.k.a. Guápiles Highway) on temporal and spatial changes in the structure of the avifauna of Braulio Carrillo National Park, Costa Rica, a site crossed by this road along 25 km. The highway connects the capital city of San José with the Harbor of Limón in the Caribbean Sea (142 km). Although the road is narrow (12 m in width and comprised by two lanes along most of the route) it services over 1.5 million motor vehicles per year, 12 % are heavy trucks and trailers. We expected the highway to divide the avifauna, and thus to observe significant differences in species structure on opposite sides of the road. We described changes in bird diversity between wet and dry seasons at Las Palmas and Ceibo trails located on opposite sides of the highway (14 point counts per trail), and evaluated how abundance and diversity varied with road distance. Censuses took place during wet and dry seasons from 2002 to 2005. We listed 245 species and 6 035 observations during the 4-yr survey. Rare species dominated the avifauna (65 % of species < 5 observations), and species overlap between trails was high (Sorensen= 71 %; Morisita= 0.96). Species accumulation curves varied little among trails, yielding 190 species. Resident species represented 70 % of observations, followed by elevational (15 %) and long-distance migrants (1-2 %). Understory species were the most abundant (60 %) followed by canopy birds (30 %). Species turnover rate was 55 % between seasons, but species composition between trails remained homogeneous. Overall, birds were avoiding the road (abundance increased away from the road) although other diversity parameters (richness, dominance, Shannon index, and equitability) were not influenced by road proximity. Although the avifauna remained homogeneous on both sides of the road, which did not support the fragmentation hypothesis, the highway reduced the abundance and diversity of specialized understory insectivores associated with primary forests near the road. This highway will expand outside the National Park (from 2 to 4 lanes along 107 km from Río Frío to Limón) in the next years, which will increase traffic volume and road impacts within the Park. Roads are increasing across highly diverse tropical areas justifying the need for management practices based on the identification of sensitive groups.